International Maritime Sales Contracts: FOB and CIF (Second Part) - Ostoja, Alfredo (1974)
In this second part of the article on F.O.B. and C.I.F. contracts in international maritime sales and purchases, the author focuses his study on the implications and considerations of the c.i.f. (cost, insurance, freight) stipulation in export trade. First, he discusses the importance of the bill of lading, as well as the marine insurance policy and the commercial invoice as key documents in these types of transactions. On this point, he refers to the customary nature of documents in international trade and the relevance of their compliance within the framework of lncoterms 1953 which, although they are not legal norms, the author recommends to adopt to avoid interpretative conflicts. Second, the obligations of the seller and buyer are developed, including aspects such as shipment of goods, contracting of transport and insurance, transfer of risks, acceptance of documents and payment of the agreed price. Then, the article examines contracts erroneously called c.i.f. and some of the variants that are admitted. Among them is the c & f (cost and freight) stipulation, which differs from c.i.f. in that the insurance is contracted by the buyer and not by the seller, and has particular significance in Peruvian law due to the enactment of Decree Law 20019 in 1973. Finally, the author highlights the commercial utility of the term c.i.f. in air trade, even though it has traditionally been used in maritime sales, emphasizing the importance of considering the legal regime of international civil aviation in this context.